2016
DOI: 10.3389/fnhum.2016.00543
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corticospinal and Spinal Excitability to the Biceps Brachii with a Neutral vs. Pronated Handgrip Position Differ between Arm Cycling and Tonic Elbow Flexion

Abstract: The purpose of this study was to examine the influence of neutral and pronated handgrip positions on corticospinal excitability to the biceps brachii during arm cycling. Corticospinal and spinal excitability were assessed using motor evoked potentials (MEPs) elicited via transcranial magnetic stimulation (TMS) and cervicomedullary-evoked potentials (CMEPs) elicited via transmastoid electrical stimulation (TMES), respectively. Participants were seated upright in front on arm cycle ergometer. Responses were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…; Forman et al. ; Nuzzo et al. ), but peripheral sources, such as inhibition from the brachioradialis (Barry et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Forman et al. ; Nuzzo et al. ), but peripheral sources, such as inhibition from the brachioradialis (Barry et al.…”
Section: Discussionmentioning
confidence: 99%
“…The pulse duration was fixed at 100 µs and stimulations intensities of 125–275 mA were used (DS7AH, Digitimer Ltd., Welwyn Garden City, Hertfordshire, UK). Stimulation intensity began at 25 mA and gradually increased until the average of 8 CMEP amplitudes matched the average of the 8 MEP amplitudes previously determined [8,28]. This stimulation intensity was used throughout the remainder of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In other studies, (Todd et al, 2003 , 2004 ; Kennedy et al, 2013 ) the elbow and shoulder joints were flexed to 90° with the forearm vertical and supinated with the force at the wrist being backwards. Changes in forearm and shoulder positions alters CSE of the biceps brachii (Forman et al, 2016 ; Nuzzo et al, 2016 ) and potentially could affect VA of the elbow flexors. Todd et al ( 2003 ) showed a high linear regression between TMS evoked SIT forces and voluntary force (50–100% MVC) in fatigued elbow flexors with the elbow and shoulder joints were flexed to 90°, which was opposite to the current results.…”
Section: Discussionmentioning
confidence: 99%